HIV infection, malnutrition, and invasive bacterial infection among children with severe malaria - Berkley, J; Bejon, P; Mwangi, T; Gwer, S; Maitland, K; Williams, T; Mohammed, S; Osier, F; Kinyanjui, S; Fegan, G; Lowe, B; English, M; et al. (University of Chicago Press, 2009)
Background. Human immunodeficiency virus (HIV) infection, malnutrition, and invasive bacterial infection (IBI) are reported among children with severe malaria. However, it is unclear whether their cooccurrence with falciparum parasitization and severe disease happens by chance or by association among children in areas where malaria is endemic. Methods. We examined 3068 consecutive children admitted to a Kenyan district hospital with clinical features of severe malaria and 592 control subjects from the community. We performed multivariable regression analysis, with each case weighted for its probability of being due to falciparum malaria, using estimates of the fraction of severe disease attributable to malaria at different parasite densities derived from cross-sectional parasitological surveys of healthy children from the same community. Results. HIV infection was present in 133 (12%) of 1071 consecutive parasitemic admitted children (95% confidence interval [CI], 11%–15%). Parasite densities were higher in HIV-infected children. The odds ratio for admission associated with HIV infection for admission with true severe falciparum malaria was 9.6 (95% CI, 4.9– 19); however, this effect was restricted to children aged ≥1 year. Malnutrition was present in 507 (25%) of 2048 consecutive parasitemic admitted children (95% CI, 23%–27%). The odd ratio associated with malnutrition for admission with true severe falciparum malaria was 4.0 (95% CI, 2.9–5.5). IBI was detected in 127 (6%) of 2048 consecutive parasitemic admitted children (95% CI, 5.2%–7.3%). All 3 comorbidities were associated with increased case fatality. Conclusions. HIV, malnutrition and IBI are biologically associated with severe disease due to falciparum malaria rather than being simply alternative diagnoses in co-incidentally parasitized children in an endemic area.